The occurrence of Salmonella spp. in duck eggs on sale at retail or from catering in England. (1st November 2016) - Owen, M.; Jorgensen, F.; Willis, C.; McLauchlin, J.; Elviss, N.; Aird, H.; Fox, A.; Kaye, M.; Lane, C.; de Pinna, E.
Abstract: Since 2010, human salmonellosis outbreaks in the UK have been detected as associated with the consumption of duck eggs. Little data are available on the rate of occurrence of Salmonella in duck eggs. The aim of this study was to investigate the occurrence of Salmonella spp. in duck eggs on sale and from catering in England during 2011, particularly those from small‐scale production. All samples were collected independently of human salmonellosis outbreak investigations. Composite samples of 6–10 eggs (shells and contents were examined separately) were examined for the presence of Salmonella spp. using the ISO 6579:2002 method. Salmonella spp. was recovered from two of 145 samples (1·4%). In one sample, Salmonella Typhimurium DT 8 was isolated from the shells while Salm . Typhimurium DT 8 and Salm . Typhimurium DT30 were isolated from the contents. Salmonella Typhimurium DT8 was isolated from the egg shells only in the second contaminated sample. This study provides baseline data for risk assessors, regulators and the food industry and may be helpful in communicating risks associated with the consumption of this product as well as evaluating risk management options to control food safety including vaccination of ducks. Significance and Impact of the Study: Human salmonellosis outbreaks in England and Northern Ireland due to Salmonella enterica serovar Typhimurium definitive phage type (DT) 8 have been identified as associated with the consumption of duck eggs since 2010. This study has shown that Salmonella spp. was detected in 1·4% of ducks egg samples providing baseline data for risk assessors, regulators and the food industry. This may be helpful in communicating risks associated with the consumption of this product as well as evaluating risk management options to control food safety including vaccination of ducks.